2022-RA-1512-ESGO Multidisciplinary and tailored management in young patients with borderline ovarian tumor recurrence: a case series. (20th October 2022) - Fais, Maria Luisa; Ungredda, Andrea; Altieri, Alfonso; Carboni, Giulia; Deo, Giuseppe; Fais, Giuseppina; Mais, Valerio; Angioni, Stefano; Peiretti, Michele
Abstract : Introduction/Background: In young women with a recurrence of borderline ovarian tumor (BOT) a second conservative treatment for the preservation of reproductive potential and endocrine function should be mandatory. In our study, we reported three cases of ovarian BOT recurrences assessed to oncofertility consultation and underwent fertility sparing surgery (FSS), highlighting the importance of the tailored clinical management in the context of a multidisciplinary meeting. Methodology: From July 2020 to April 2022, we managed three cases of young women with controlateral ovarian BOT recurrence after unilateral adnexectomy. Median age at diagnosis was 26 years (I.Q.R 25–28). After multidisciplinary meeting each patient has been addressed to oncofertility consultation with the gynecologic oncologist and the reproductive physician. Two patients had strong desire to conceive furthermore they underwent a controlled ovarian hyperstimulation (COH) with concomitant letrozole and ovarian cryopreservation. In one case the ART (assisted-reproductive-technology) procedures has been performed with tumor onsite. Results: Second surgery consisted in unilateral laparoscopic cystectomy in all cases. In those patients who have undergone COH, two and five mature oocytes were cryopreserved, respectively. After 11 months of surgery one patient became pregnant spontaneously and she gave birth at 39 weeks with an excellent obstetrical outcome. In one case the oocytes cryopreservation has been rejected by the patient, but the endocrine function has been preserved. Conclusion: In young women, with BOT ovarian recurrence, a second conservative treatment should be always considered and an oncofertility consultation should be recommended. Clinical management must be tailored on a case-by-case basis by a gynecologic oncologist and reproductive physician meeting.